End-timers: three thousand years of waiting for Judgment Day - Ballard, Martin (Praeger, 2011)
Fighting the dragon of chaos: beginnings -- David's righteous branch: the Jewish end-time -- The secret of the kingdom: the Christian end-time -- The book shall be laid down: the Islamic end-time -- The day of Antichrist approaches: Europe before 1346 -- Do not let your sword cool: plague and reformation -- Everything that is hidden is found: mystics and explorers -- Before the end of the world come: a Messianic century -- In the hands of an angry God : end-timers in conflict -- When the Master comes: Messiah and Mahdi -- No other goal than Palestine: Zionists and politicians -- Signs of the times: a troubled world